Factors that Influence Information Systems for Competitive Advantage: Human Resources, Information Technology and Organizational Support - Sjarifudin, Didin; Ali, Hapzi (Dinasti International Journal of Digital Business Management, 2023)
Research related to factors that influence information systems for competitive advantage: human resources, information technology and organizational support is a literature review research article. The purpose of writing this article is to build a research hypothesis on the influence between variables, which is useful for further research within the scope of human resource management. This type of research is in the form of a literature review in the form of qualitative research which is sourced from previous research that has been published. Previous research sources such as Google Scholar, digital reference books, DOAJ and SINTA. The results of this literature review research are: 1) Human resources influence information systems for competitive advantage; 2) Information technology influences information systems for competitive advantage; and 3) Organizational support influences information systems for competitive advantage.